Grape Seed Extract Attenuates Hepatitis C Virus Replication and Virus-Induced Inflammation - Chen, Wei-Chun; Tseng, Chin-Kai; Chen, Bing-Hung; Lin, Chun-Kuang; Lee, Jin-Ching (Frontiers in Pharmacology, 2016)
Hepatitis C virus (HCV) infection is a causative factor leading to hepatocellular carcinoma due to chronic inflammation and cirrhosis. The aim of the study was first to explore the effects of grape seed extract (GSE) in HCV replication, and then to study mechanisms. The results indicated that a GSE treatment showed significant anti-HCV activity and suppressed HCV-elevated cyclooxygenase-2 (COX-2) expression. In contrast, exogenous COX-2 expression gradually attenuated antiviral effects of GSE, suggesting that GSE inhibited HCV replication by suppressing an aberrant COX-2 expression caused by HCV, which was correlated with the inactivation of IKK-regulated NF-κB and MAPK/ERK/JNK signaling pathways. In addition, GSE also attenuated HCV-induced inflammatory cytokine gene expression. Notably, a combined administration of GSE with interferon or other FDA-approved antiviral drugs revealed a synergistic anti-HCV effect. Collectively, these findings demonstrate the possibility of developing GSE as a dietary supplement to treat patients with a chronic HCV infection.